2019
DOI: 10.1038/s41586-019-0895-y
|View full text |Cite
|
Sign up to set email alerts
|

PKG1-modified TSC2 regulates mTORC1 activity to counter adverse cardiac stress

Abstract: SUMMARYThe mechanistic target of rapamycin complex-1 (mTORC1) coordinates regulation of growth, metabolism, protein synthesis, and autophagy1. Its hyper-activation contributes to disease in many organs including the heart1,2, though broad mTORC1 inhibition risks interference with its homeostatic roles. Tuberin (TSC2) is a GTPase-activating protein and prominent intrinsic regulator of mTORC1 by modulating Rheb (Ras homolog enriched in brain). TSC2 constitutively inhibits mTORC1, but this activity is modified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 31 publications
(36 reference statements)
5
94
0
Order By: Relevance
“…2a ). In a prior Mass Spec-derived database of proteins in adult rat myocytes subjected to 15 minutes PKG activation 25 , we found CHIP modified at S20 (S20 in rat and mouse, S19 human, Fig. 2b ), a highly conserved residue in the TPR domain (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2a ). In a prior Mass Spec-derived database of proteins in adult rat myocytes subjected to 15 minutes PKG activation 25 , we found CHIP modified at S20 (S20 in rat and mouse, S19 human, Fig. 2b ), a highly conserved residue in the TPR domain (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…While this study focused on the impact of PKG on CHIP, studies have also shown the kinase modifies many other pathways relevant to myocardial pathological signaling and remodeling 34 , and these could also have contributed to the net effects observed. Among these mechanisms are PKG-mediated mitochondrial protection and cytoprotection against ischemia/infarction 35 , activating the regulator of G-protein signaling proteins RGS2 and RGS4 to inhibit Gq-receptor coupled signaling, blocking transient receptor potential canonical channel 6 to blunt fibrosis and hypertrophy 36 , 37 , and activating tuberous sclerosis complex 2 (TSC2) to blunt the mechanistic target of rapamycin complex-1 (mTORC1) stimulating autophagy and reducing pathological growth 25 . Specific to the UPS, PKG activates the 26S proteasome enhancing degradation of damaged/misfolded proteins in models of heart disease and neurodegenerative 22 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that TSC2 phosphorylation by protein kinase G1 (PKG1) can prevent cardiac hypertrophy in response to pressure overload by suppressing mTORC1 signaling. Importantly, phosphorylation of PKG1 target sites in TSC2 does not affect the basal level of mTOR activity [68]. Together, these studies indicate that targeting of the specific regulatory components of mTORC1 may provide effective therapies while minimizing off target effects associated with inhibition of the mTORC kinase itself.…”
Section: Mtorc1mentioning
confidence: 85%
“…Hence, PKG is anti-adrenergic. PKG also phosphorylates tuberin (TSC2), restraining mammalian target of rapamycin complex 1 (mTORC1) activity [24]. In this way, PKG regulates basal cardiac contractility, lowering inotropy and raising lusitropy, and precludes cardiac hypertrophy, fibrosis and apoptosis.…”
Section: Cyclic Nucleotides In Cardiac Physiologymentioning
confidence: 99%